Investigation of hand index, digit finger ratio (2D:4D), and grip strength among court sports - Rahman, Md. Hamidur; Sharma, J.P. (Anthropological Review, 2024)
Hand index, finger ratio, and grip strength are potential indicators of proficiency in court sports. The aim of this study is to explore hand dimensions, fingers length ratio, and grip strength in court sports players, a domain in which such characteristics can significantly influence performance. Measurements, such as hand length (HL), hand breadth (HB), hand index (HI), palm length (PL), hand span (HS), index finger length (2D), ring finger length (4D), 2D to 4D ratio (2D:4D), low digit ratio (LDR), and high digit ratio (HDR) were studied in the field of hand anthropometry, along with a handgrip strength (HGS) test. Data were obtained from 135 male court sports players, including basketball, handball, and volleyball, with 45 players from each discipline. Descriptive statistics, one-way ANOVA, and an independent t-test were used to compare variables, with statistical significance set at p < 0.05. The ANOVA results indicated that there were no significant differences in hand variables, namely HL, HB, PL, HS, 2D, 4D, 2D:4D, LDR, HDR, and HGS, except for the HI variable. Post-hoc test results showed HI differences in basketball versus handball and volleyball. Compared to standard HI, their ranges show that all-court sports often fall into the Dolichocheri type, characterized by long fingers and a narrow, small palm. A low digit ratio may have some effect on HI in basketball and volleyball. However, it does not appear to have a significant effect on HGS across the study. In summary, the results of our study show that court athletes are similar in hand characteristics, 2D:4D, and grip strength for the nature of the game.